Overview of cultivated and wild species of the Bignoniaceae family in the Emirate of Fujairah (United Arab Emirates) - Byalt Vyacheslav Vyacheslavovich; Korshunov Mikhail Vladimirovich (Hortus Botanicus)
The article provides an overview of the family Bignoniaceae in the flora of the emirate of Fujairah, located in the mountainous northeastern part of the United Arab Emirates (UAE). We studied the flora of the emirate for 6 years, from 2017 to 2022. As a result of field research, examination of irrigated gardens, public parks, urban plantings and plant nurseries, herbarium materials and literature data, a list of wild and cultivated plant species growing here was compiled. The article provides an annotated list of representatives of the Bignoniaceae (introduced and native), which we identified in the emirate of Fujairah, including both literature and herbarium data, and data from the authors based on the results of original surveys of the territory of the emirate as of the spring of 2024. Genera and species are arranged in alphabetical order ok. The family list is given within the administrative boundaries of Fujairah, both for natural habitats and for public places: city gardens and parks, boulevards and embankments, squares, streets and local areas. Data on species found in plant nurseries were taken into account. The list contains 18 species from 12 genera. Native and alien, cultivated (ergasiophytes) and wild from cultivation (ergasiophygophytes – ephemerophytes, colonophytes and epoecophytes) -Tecomella undulata (Sm.) Seem. native or naturalized species; Spathodea campanulata P. Beauv., Tecoma stans (Linn.) Juss. ex Kunth, Millingtonia hortensis Linn. f. is listed as a new alien species for Fujairah. A number of species – Handroanthus impetiginosus (Mart. ex DC.) Mattos, Radermachera sinica (Hance) Hemsley, Tabebuia aurea (Silva Manso) Benth. & Hook. f. ex S. Moore, Tecoma × smithii Wittmack are listed for the first time as introduced and runing wild or alien species for Fujairah, the UAE and Arabia as a whole.